Vortex generator design and numerical investigation for wake non-uniformity and cavitation fluctuation pressure reduction. (1st June 2021) - Li, Liang; Zhou, Bin; Huang, Hongbo; Sun, Hongxing
Abstract: Aiming at the problem that the exciting force induced by the propeller is excessive and the hull vibration noise exceeds certain limits for a certain surface ship, a type of triangular vortex generator is designed in this paper which is installed on the surface of ship stern to improve the quality of ship wake and solve the vibration problem. Firstly, the size and installing position of the vortex generator are designed based on the ship body lines. Then, the numerical calculation is conducted both for the bare hull and "hull-propeller-vortex generator" system to investigate the effectiveness of the vortex generator. With the installation of the vortex generator, the wake changes mainly occur in the region near the 12 o'clock. The velocity in the high wake area gains effective acceleration and the circumference transition of wake becomes more moderate which contributes to the smooth transition of the blade unsteady cavitation in circumference direction. What's more, the changes of wake can delay the circumference angle of the blade cavitation collapse. It increases the distance between the positions where the blade cavitation collapsed and the ship bottom shell. It is also beneficial to reduce the amplitude of fluctuating pressure. The calculated results show that the fluctuation pressure energy is spread from 1st, 2nd to 3rd or more high-order harmonic components with help of vortex generator. So, the level of fluctuation pressure drops significantly for the 1st and 2nd harmonic components which are the main exciting sources for the hull vibration. Highlights: The size and installing position of the vortex generator are designed based on the ship body lines. The circumference transition of wake becomes more moderate with the installation of vortex generator. The vortex generator can delay the circumference angle of the blade cavitation collapse to reduce fluctuation pressure. Fluctuation pressure energy is spread from 1st, 2nd to 3rd or more high-order harmonic components with the help of .